In vitro antioxidant and cytotoxic activity of Zanthonitrile isolated from Zanthoxylum alatum - Indrajit Karmakar, Sagnik Haldar, Mainak Chakraborty, Saikat Dewanjee, Pallab Kanti Haldar (Journal of Applied Pharmaceutical Science, 2016)
The present study evaluates the antioxidant and cytotoxic activity of Zanthonitrile isolated from Zanthoxylum alatum leaves. The structure of Zanthonitrile [{4-[(3-Methyl-2-buten-1-yl) oxy] phenyl} acetonitrile] was elucidated form the data obtained from UV, IR, Mass, and NMR. The in vitro antioxidant activity of Zanthonitrile was estimated by standard 1, 1-diphenyl-2-picrylhydrazil radical (DPPH) scavenging assay method. In vitro cytotoxicity was determined in Ehrlich Ascites Carcinoma (EAC) cells by MTT assay. The compound exhibited antioxidant activity in a dose dependent manner. The IC50 value of Zanthonitrile for DPPH was estimated to be 7.86 ± 0.23 μg/mL. Zanthonitrile showed satisfactory cytotoxic potential in MTT assay with the IC50 value 57.28 ± 0.64 μg/mL. Satisfactory results of both the studies correlate each other and further investigations will focus on in vivo models and cell cycle to determine the role on intrinsic and extrinsic apoptotic pathways.
Keywords: Zanthonitrile,Zanthoxylum alatum, cytotoxicity, antioxidant.